2006
DOI: 10.1002/micr.20245
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of shoulder function with nerve transfers in traumatic brachial plexus palsy patients

Abstract: Shoulder stabilization is of utmost importance in upper extremity reanimation following paralysis from devastating injuries. Although secondary procedures such as tendon and muscle transfers have been used, they never achieve a functional recovery comparable to that following successful reinnervation of the supraspinatus, deltoid, teres minor, and infraspinatus muscles. Early restoration of suprascapular and axillary nerve function through timely brachial plexus reconstruction offers a good opportunity to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…18 But in the more frequent lesions caused by traction on the arm, nerve lesions show extensive scarring, and a large resection of the already-retracted nerve ends has to be performed until acceptable nerve stumps are available. This procedure greatly increases the necessary length of the nerve grafts, often over 7 cm, 19 hence the gain in nerve length observed by humeral shortening of 6 cm is insufficient in most brachial plexus lesions, except perhaps in selected gunshot wounds or lacerations.…”
Section: Discussionmentioning
confidence: 98%
“…18 But in the more frequent lesions caused by traction on the arm, nerve lesions show extensive scarring, and a large resection of the already-retracted nerve ends has to be performed until acceptable nerve stumps are available. This procedure greatly increases the necessary length of the nerve grafts, often over 7 cm, 19 hence the gain in nerve length observed by humeral shortening of 6 cm is insufficient in most brachial plexus lesions, except perhaps in selected gunshot wounds or lacerations.…”
Section: Discussionmentioning
confidence: 98%
“…In axillary nerve reconstruction, good results have been obtained using the 1) spinal accessory nerve (60%), 27 2) phrenic nerve (66%), 27 3) intercostal nerves (33%-67%), 14,19,33 4) thoracodorsal nerves (36%-93%), 23,28 5) C-5 and/or C-6 root via nerve grafts (67%), 34 or 6) the contralateral C-7 root (52%) as the donor of motor nerve fibers. 31 Recently, successful neurotization using a branch of the radial nerve for the triceps muscle as donor was performed with very good results.…”
mentioning
confidence: 99%
“…Terzis et al 12 reported that the SSN is vulnerable at 3 points: (1) as it leaves the upper trunk, (2) at the suprascapular notch, and (3) at the spinoglenoid notch where it bends around the spine of the scapula. The nerve may be injured directly by bone fragments when the fracture is located at the spinoglenoid notch.…”
Section: Discussionmentioning
confidence: 98%